وطافراتها في تثبيت النتروجين Azotobacter vinlndiiفي نمو وكفاءة بكتريا Eucalyptus camaldulensisتأثير المستخلص المائي لاوراق نبات - الكبيسي سناء سعود (Al-Nahrain Journal of Science, 2010)
The study was included isolation andidenfication of 30 bactrial isolates forAzotobacter vinlandii from agricultural soils inBaghdad governorate .On the base ofmicroscobical, morphological characteristicsof cell and colonies also the best growth ,strain was choosen, The Mutants thatdeveloped resistant to the antibiotics(streptomycin, pencillin) was selected. Themutant showed best Nitrogen fixation waschoosen. The aqueous extract of Eucalyptus leaves with (5-10%) cocentartion activity (inculture medium) on total count and totalnitrogen cocentartion for wild type andmutants was stuidied.Results of present study showed that theleaves extract inhibited the numbers ofnitrifying bactria and its total nitrogen of wildtype and mutants. Mutants strains were moresesitive to the used concetration. Theinhibition value was increased when theconcetration of extract was increased from 5 to10%. The inhibtion values were (69.4, 93.4%)to bactrial count of wild type and streptomycinmutant resistant resepectively. And (90.2,97.9%) to total nitrogen for both of themrespectively. Wherease resistant to penicillinmutant was unable to grow on anyconcentration for Eucalyptus extractes